1931
DOI: 10.1021/ie50254a023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cod-Liver Oil on Calcium Metabolism of Young Chicks

Abstract: The poultry industry contributes materially to the agricultural income of this country and constitutes a valuable home market for a large amount of wheat, corn, other grains, and by-products of the packing-house, dairy, and fishing industries. The increased per capita consumption of poultry and eggs, coupled with the perfection of artificial incubation and brooding equipment, has revolutionized the poultry industry, placing poultry raising on a mass-production basis. Formerly chickens were raised during the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1931
1931
1940
1940

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…29 Hendricks and coworkers (74) heated mixtures of calcium carbonate and "hydrated tricalcium phosphate" or "pure" hydroxyapatite to con-27 Many years before x-rays were known or applied in this field, the composition of bony substances and their chemical behavior led to the assumption that an apatite was present (1,85,225). Numerous analyses show an approximately constant mole ratio of Ca:P = 10:6 for many kinds of bone under a wide variety of conditions (20,22,28,29,63,64,80,81,87,107,122,137,152,195,200,204,205,209,225). stant weight at 900°C.…”
Section: The Inorganic Constituents Of Bone26mentioning
confidence: 99%
“…29 Hendricks and coworkers (74) heated mixtures of calcium carbonate and "hydrated tricalcium phosphate" or "pure" hydroxyapatite to con-27 Many years before x-rays were known or applied in this field, the composition of bony substances and their chemical behavior led to the assumption that an apatite was present (1,85,225). Numerous analyses show an approximately constant mole ratio of Ca:P = 10:6 for many kinds of bone under a wide variety of conditions (20,22,28,29,63,64,80,81,87,107,122,137,152,195,200,204,205,209,225). stant weight at 900°C.…”
Section: The Inorganic Constituents Of Bone26mentioning
confidence: 99%
“…Tully et al (1931), using oyster shells or limestone meal with steamed bone meal, found that a Ca/P ratio of 3.3:1 gave the best results. Holmes and Pigott (1931) observed that the best growth and Ca utilization was obtained on diets supplemented with cod liver oil, containing from 1 percent to 4 percent Ca., and having a maximum Ca/P ratio of 1.5:1. Widening the Ca/P ratio resulted in poor growth and bone development.…”
mentioning
confidence: 96%
“…With a minimum supply of vitamin D the ratio is more limited than with an adequate one. Holmes and Pigott (1931) obtained the best growth with a ration having a maximum calcium-phosphorus ratio of 1.5:1.0.…”
mentioning
confidence: 97%